2016
DOI: 10.1007/978-3-319-43958-7_49
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Segmentation in i-Vector Based Speaker Diarization of Telephone Speech

Abstract: Abstract. The goal of this paper is to evaluate the contribution of speaker change detection (SCD) to the performance of a speaker diarization system in the telephone domain. We compare the overall performance of an i-vector based system using both SCD-based segmentation and a naive constant length segmentation with overlapping segments. The diarization system performs K-means clustering of i-vectors which represent the individual segments, followed by a resegmentation step. Experiments were done on the Englis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…It is assumed that any inaccuracies can be resolved during the later stages of the diarization process, typically by performing a final resegmentation step. This was also confirmed in our recent paper [16], which compared the fixed length approach with SCD-based segmentation using GLR distance. There, we showed that even though the SCD approach led to better initial clusters, the final results of both options after resegmentation were comparable.…”
Section: Introductionsupporting
confidence: 78%
See 4 more Smart Citations
“…It is assumed that any inaccuracies can be resolved during the later stages of the diarization process, typically by performing a final resegmentation step. This was also confirmed in our recent paper [16], which compared the fixed length approach with SCD-based segmentation using GLR distance. There, we showed that even though the SCD approach led to better initial clusters, the final results of both options after resegmentation were comparable.…”
Section: Introductionsupporting
confidence: 78%
“…The specific implementation largely follows the descriptions presented in our previous papers [8,16] and a diagram of the main steps can be seen in Fig. 1.…”
Section: Offline Diarization Systemmentioning
confidence: 99%
See 3 more Smart Citations